Phenotypic evaluation of ten sugarcane (Saccharum officinarum L.) genotypes at Finchaa Sugar Estate, Ethiopia - Mekonnen Shitahun Alemu; Azene Tesfaw Fetene (Ratarstvo i Povrtarstvo, 2022)
The aim of the study was to evaluate ten introduced sugarcane genotypes for yield and juice quality in three successive crop cycles at Finchaa Sugar Estate, Ethiopia. Eight sugarcane genotypes were grown from December 2016 to May 2020 laid in a CRBD with three replications. Data were collected for number of internodes, millable stalk, plant height, stalk girth, single cane weight, cane yield, brix percent juice, pol percent, and sugar recovery percentage and sugar yield. The collected data was subjected to analysis of variance with the help of statistical analysis system software and treatment means were separated using least significance difference method at 5% level of significance. Analysis of variance for the three crop cycles indicated the existence of variation between genotypes in all quantitative traits. In the mean comparisons of traits for the three crop cycles, the genotype CP 96 12 52 had the highest number of millable stalks and VMC 96 273 and MPT 96 035 produced the highest cane thickness and single stalk weights. Considering sugar yield the best sugarcane genotypes were N 14, CP 96 1252, CPCL 02 926 and VMC 96 89 respectively. N 14 was the highest performed variety in cane and sugar yield, but its sugar recovery percent performance was very low (10.32%). However, CP 96 1252, CPCL 02 926 and VMC 96 89 had the highest sugar recovery percentage 12.93%, 14% and 12.15% respectively and had been recommended for timely seed increase for verification in large plots at Finchaa Sugar Estate.